Additional phenanthrene alkaloid isolated from the leaves of Cryptocarya nigra (Lauraceae) - Ayu Afiqah Nasrullah (Pusat e-pembelajaran, UMS, 2021)
Previous studies on alkaloidal constituents isolated from the bark of Cryptocarya nigra (Lauraceae), a perennial widely distributed in the forest of Malaysia, have revealed that it is a good source of phenanthrene alkaloids 2-4. The phytochemical study of this bark extract has led to the isolation and characterization of three known phenanthrene alkaloids: 2-hydroxyathersperminine 2, atherosperminine 3, and noratherosperminine 4. The author now reports the isolation, identification and chracterisation of an additional known phenantrene alkaloid, argentinine 1, where the plant specimens were collected from Hutan Simpan Ulu Sat, Machang, Kelantan (Malaysia). Structural elucidation of argentinine 1 alkaloids was established through several spectroscopic methods such as 1D-NMR, IR, UV and LCMS, and comparison with published data.